Cinematic Vitalism - Pollmann, Inga (Film Culture in Transition, 2017)
This book draws new connections between twentieth-century German and French film theory and practice and vitalist conceptions of life from biology and philosophy. Inga Pollmann shows how the links between the two created a modernist, experimental, and cinematic strand of vitalism in and around the movie theater. Articulated by film theorists, filmmakers, biologists, and philosophers, this cinematic vitalism maps out connections among human beings, milieus, and technologies that continue to structure our understanding of film.